Fundamentals of silicene - Willatzen, Morten (2017)
Silicene is a single atomic layer of silicon (Si) much like graphene, the first example of an elemental twodimensional (2D) nanomaterial whose study led to the 2010 Nobel Prize in Physics. Until 2010 or so, the only known crystalline form of elemental silicon was the one with the so-called diamond structure (a three dimensional cubic structure with sp3 -bonded Si atoms). That silicon could potentially form a 2D structure was first postulated by Takeda and Shiraishi. This early work and others, both theoretical and experimental,8,9 went mostly unnoticed until the prediction that silicene could have similar exotic properties as graphene by Guzmán-Verri and Lew Yan Voon in 2007, and silicene nanoribbons were reported to have been fabricated on a silver substrate by Kara et al. in 2009. Since then, the study of silicene has exploded, mainly theoretically but also experimentally. The interest in silicene is exactly the same as that for graphene2: in being two-dimensional and possessing a linear band structure, the so-called Dirac cone. One advantage relies on its possible application in electronics, whereby its natural compatibility with the current Si technology might make fabrication much more of an industrial reality. We will concentrate this tutorial on the properties of a single freestanding silicene sheet. Freestanding means that the silicene sheet is not chemically or physically bonded to any other material. The feat with graphene was the ability to peel off a single layer of graphene from a piece of graphite, a process known as mechanical exfoliation. Such a layered precursor is missing for silicene. A close analogue, though, is calcium disilicide, indeed a layered material and the related process of chemical exfoliation has been tried, with only partial success as the resulting product was mostly multilayers and functionalized. Not surprisingly, a number of review articles have already appeared that includes extensive discussions of silicene. The current review is more tutorial in nature.